Essential Oil Composition of Aloysia gratissima From Brazil - Trovati, Graziella; Chierice, Gilberto O.; Sanches, Edgar A.; Galhiane, Mario Sergio [UNESP] (Allured Publ Corp, 2009)
The study of Aloysia gratissima essential oil from leaves was obtained by hydrodistillation using a Clevenger type apparatus. The essential oil composition was analyzed by GC and GC/MS. The major compounds were identified representing 94.7% of the oil. The most abundant compounds were isopinocamphone (cis-3-pinanone) (25.4%), limonene (15.1%), and guaiol (12.7%).
Keywords: Aloysia gratissima; Verbenaceae; essential oil composition; isopinocamphone; limonene; guaiol